Stroke in Asia: An epidemiological consideration - A. Viriyavejakul (2018)
Although the study of the epidemiology of stroke in developed Western countries (as judged from the number of relevant articles published in international medical journals) is extensive, in Asian countries it has been comparatively limited (with the exception of Japan). Many of the studies from Asian countries also appear to be deficient, thus making comparison between the countries difficult. In addition, many of these studies are believed to be published in local journals not usually cited and difficult to retrieve from, and relevant and retrievable data from many developing countries often show considerable time lapse, making a meaningful comparison between countries even more difficult. In Thailand, Public Health Statistics show that stroke has been on the increase. Taken as an example, the death rate from cerebrovascular disease (CVD) was 3.7/100,000 in 1950, rising to 6.7/100,000 in 1970, and to 11.8/100,000 in 1983. In 1984, there were 9,414 cases of CVD admitted to hospitals in Thailand. The incidence (in patients) increased from 12.7/100,000 in 1981 to 18.7/100,000 in 1984. Since 1957, the mortality rate has been steadily increasing, from ~1/100,000 to ~6/10,000. In a survey taken in 1983 of a medium-size community in Bangkok, it was found that the prevalence of CVD was 6.9/1,000. The same Public Health Statistics also showed that the rate of immediate death after stroke (which is defined as death within 4 weeks after the onset) from nonembolic cerebral infarction, cerebral embolism, and cerebral hemorrhage was reported to be 19.5, 37, and 85% respectively. Considerable difference was noted in the death rates from CVD in various Asian countries. In 1970, the number of deaths per 100,000 in Japan was reported to be 174.9, whereas in other countries these figures (per 100,000) were: Malaysia, 15.9 (in 1981); Hong Kong, 45.8 (in 1970); and Singapore, 50.2 (in 1971). The reported data from some countries are considered too low, possibly the result of the method of collection of public health data.